Studi Karakteristik Jagung Introduksi Dan Beberapa Varietas Jagung Lokal - Wika Winani Syahputri Syahputri; Hot Setiado; Khairunnisa Lubis (Jurnal Agroekoteknologi, 2018)
The research was aimed to know the characteristics of vegetative and generative of introduction and some local maize varieties. The research was carried out on the land of the Centre Seed Service of Cash Crops, Departmentof Agriculture, Medan Sunggal, Deli Serdang district, from July 2016 to October 2016. The randomized block design was used with three varieties of maize (Black Aztec, Bisi2, Bonanza). Variables observed were: the plant height, the time of flowering, the time of female flowers bloomed, the time of harvested, the cob length, the number of lines per cob, the production per sample plant, the production per plot. The results showed that the three varieties of maize tested have varying diversity to the plant height, the time of male flower bloomed, the time of harveste, the cob length, the number of line per cob, the production per sample, the production per plot. The Black Aztec showed the lowest production (1005.56 grams per plot) mean while the Bonanza showed the highest production (2338.44 grams). The highest heritability and the broad of diversity coefficient  were obtained in the time of male flower bloomed, the time of female flower bloomed, the time of harvested, the number of lines per cob.Key words: introduction, maize, varieties